Synthesis, antimicrobial and antioxidant activities of pyridyl substituted thiazolyl triazole derivatives - Tay, Naime Funda; Duran, Murat; Kayagil, Ismail; Yurttas, Leyla; Goger, Gamze; Goger, Fatih; Demirayak, Seref (Univ Sao Paulo, Conjunto Quimicas, 2022)
In this present study, 63 different 5-[4-methyl-2-(pyridin-3/4-yl)thiazole-5-yl]-4-substituted-3-substituted benzylthio-4H-1,2,4-triazole derivatives were synthesized, and evaluated for their in vitro antimicrobial activity against various human pathogenic microorganisms and antioxidant activity. The derivatives were synthesized in a multi-step synthesis procedure including triazole and thiazole ring closure reactions, respectively. The synthesized derivatives (A1-24; B1-39) were screened for their antibacterial, antifungal, and antioxidant activities compared to standard agents. The derivatives possessing 3-pyridyl moiety particularly exhibited relatively high antibacterial activity (MIC= < 3.09-500 mu g/mL) against Gram-positive bacteria, and compounds possessing 4-pyridyl moiety showed remarkable antioxidant activity.
Keywords: Triazole; Thiazole; Pyridine; Antimicrobial activity; Antioxidant activity; DPPH radical scavenging